ECG Changes Through Immunosuppressive Therapy Indicate Cardiac Abnormality in Anti-MDA5 Antibody-Positive Clinically Amyopathic Dermatomyositis - Matsuo, Takashi; Sasai, Tsuneo; Nakashima, Ran; Kuwabara, Yoshihiro; Kato, Eri Toda; Murakami, Isao; Onizawa, Hideo; Akizuki, Shuji; Murakami, Kosaku; Hashimoto, Motomu; Yoshifuji, Hajime; Tanaka, Masao; et al. (Frontiers in Immunology, 2022)
Anti-melanoma differentiation-associated gene 5 (MDA5) antibody, a dermatomyositis (DM)-specific antibody, is strongly associated with interstitial lung disease (ILD). Patients with idiopathic inflammatory myopathy (IIM) who are anti-MDA5 antibody positive [anti-MDA5 (+)] often experience chest symptoms during the active disease phase. These symptoms are primarily explained by respiratory failure; nevertheless, cardiac involvement can also be symptomatic. Thus, the aim of this study was to investigate cardiac involvement in anti-MDA5 (+) DM. A total of 63 patients with IIM who underwent electrocardiography (ECG) and ultrasound cardiography (UCG) during the active disease phase from 2016 to 2021 [anti-MDA5 (+) group, n = 21; anti-MDA5-negative (-) group, n = 42] were enrolled in the study, and their clinical charts were retrospectively reviewed. The ECG and UCG findings were compared between the anti-MDA5 (+) and anti-MDA5 (-) groups. All anti-MDA5 (+) patients had DM with ILD. The anti-MDA5 (+) group showed more frequent skin ulcerations and lower levels of leukocytes, muscle enzymes, and electrolytes (Na, K, Cl, and Ca) than the anti-MDA5 (-) group. According to the ECG findings obtained during the active disease phase, the T wave amplitudes were significantly lower for the anti-MDA5 (+) group than for the anti-MDA5 (-) group (I, II, and V4–6 lead; p < 0.01; aVF and V3, p < 0.05). However, the lower amplitudes were restored during the remission phase. Except for the E wave, A wave and Sep e’, the UCG results showed no significant differences between the groups. Four patients with anti-MDA5 (+) DM had many leads with lower T wave and cardiac abnormalities (heart failure, diastolic dysfunction, myocarditis) on and after admission. Though anti-MDA5 (+) patients clinically improved after immunosuppressive therapy, some of their ECG findings did not fully recover in remission phase. In conclusion, anti-MDA5 (+) DM appears to show cardiac involvement (electrical activity and function) during the active phase. Further studies are necessary to clarify the actual cardiac condition and mechanism of these findings in patients with anti-MDA5 (+) DM.